A role of SAND-family proteins in endocytosis. (1st August 2005) - Poteryaev, D.; Spang, A.
Abstract : Caenorhabditis elegans has recently been used as an attractive model system to gain insight into mechanisms of endocytosis in multicellular organisms. A combination of forward and reverse genetics has identified a number of new membrane trafficking factors. Most of them have mammalian homologues which function in the same transport events. We describe a novel C. elegans gene sand-1, whose loss of function causes profound endocytic defects in many tissues. SAND-1 belongs to a conserved family of proteins present in all eukaryotic species, whose genome is sequenced. However, SAND family has not been previously characterized in metazoa. Our comparison of C. elegans SAND-1 and its yeast homologue, Mon1p, showed a conserved role of the SAND-family proteins in late steps of endocytic transport.